TINJAUAN KESEHATAN DAN KESELAMATAN KERJA ASPEK FISIK TERHADAP PETUGAS REKAM MEDIS BAGIAN PENYIMPANAN BERKAS DI RUMAH SAKIT ANGKATAN UDARA (RSAU) DR. M. SALAMUN BANDUNG - Harto, Suharto Harto; Nailufar, Ishmah (Jurnal TEDC; Vol 17 No 3 (2023): JURNAL TEDC, 2023)
Based on the results of a preliminary study conducted by the authors at RSAU Dr. M. Salamun Bandung found a problem that the officers did not use Personal Protective Equipment (PPE), many boxes containing medical record documents were scattered on the floor making it difficult for officers to take or enter files, and only one tool was available in the form of an iron ladder. There was once an officer who fell from a ladder and was exposed to a cold cough due to unclean air as many as 2 people. The purpose of this study was to provide an overview of the physical aspects in the medical record storage room based on occupational health and safety at RSAU Dr. M. Salamun Bandung. The research method used is descriptive qualitative method and observational method with a cross sectional approach. Data collection techniques used are observation, interviews, literature studies, and documentation. The subjects in this study were medical record file keepers at RSAU Dr. M. Salamun Bandung with occupational health and safety research objects, namely lighting, ventilation, temperature, and infrastructure/personal protective equipment. The results of the author's research, that the storage room for medical record files is already in a strategic place that is easy to reach by officers. However, there is still a mismatch in room conditions in terms of lighting, ventilation, temperature, and infrastructure as well as officers who do not use personal protective equipment. The author's conclusions and suggestions are to improve the lack of lighting, repair damaged air conditioners, add sinks, and the hospital conducts training on occupational health and safety for officers so they know the impacts that arise while working, and requires officers to use PPE.